2002
DOI: 10.1074/jbc.m107150200
|View full text |Cite
|
Sign up to set email alerts
|

Chimaerins, Novel Non-protein Kinase C Phorbol Ester Receptors, Associate with Tmp21-I (p23)

Abstract: The regulation and function of chimaerins, a family of "non-protein kinase C" (PKC) phorbol ester/diacylglycerol receptors with Rac-GAP activity, is largely unknown. In a search for chimaerin-interacting proteins, we isolated Tmp21-I (p23), a protein localized at the perinuclear Golgi area. Remarkably, phorbol esters translocate ␤2-chimaerin to the perinuclear region and promote its association with Tmp21-I in a PKC-independent manner. A deletional analysis revealed that the C1 domain in chimaerins is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 47 publications
7
87
1
1
Order By: Relevance
“…A cytosolic protein PKC has been shown to play an important role in platelet aggregation by pharmacological experiments using cell-permeable small compounds of inhibitors and stimulators such as phorbol esters (16,17). However, the results obtained from such experiments appear somewhat indirect because the specificity of inhibitors is not absolutely strict and important signaling molecules containing the phorbol ester-binding C1 domain other than PKC have been recently identified such as Ras-guanyl nucleotide-releasing protein (11,12) and chimerin (13,14). Munc13-1 present in the presynapse also contains the C1 domain (38), and it has very recently been demonstrated that the effect of phorbol ester in the neurotransmitter release is through Munc13-1 (39).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A cytosolic protein PKC has been shown to play an important role in platelet aggregation by pharmacological experiments using cell-permeable small compounds of inhibitors and stimulators such as phorbol esters (16,17). However, the results obtained from such experiments appear somewhat indirect because the specificity of inhibitors is not absolutely strict and important signaling molecules containing the phorbol ester-binding C1 domain other than PKC have been recently identified such as Ras-guanyl nucleotide-releasing protein (11,12) and chimerin (13,14). Munc13-1 present in the presynapse also contains the C1 domain (38), and it has very recently been demonstrated that the effect of phorbol ester in the neurotransmitter release is through Munc13-1 (39).…”
Section: Discussionmentioning
confidence: 88%
“…For example, Ras-guanyl nucleotide-releasing protein (11,12) contains the C1 domain at its C terminus and acts as a stimulator for small GTPase Ras involved in the regulation of cell growth. Chimerin (13,14) also contains a C1 domain and acts as a GTPase-activating protein of small GTPase Rac involved in the regulation of cytoskeletal reorganization. Thus, the effects of phorbol esters could be through multiple pathways.…”
mentioning
confidence: 99%
“…2 Based on those results, we surmise that the localization of RasGRP1 in the endoplasmic reticulum is helped by the binding of the RasGRP1 ZF to a docking protein present in that subcellular compartment. A similar targeting mechanism has been proposed recently for chimerins (21), a group of phorbol ester receptors that act as GAPs for Rho/Rac GTPases (20). We are currently conducting yeast two-hybrid experiments to characterize the possible binding partners for the RasGRP1 ZF domain in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 DAG is a lipid second messenger generated directly by the action of phospholipase C isozymes or indirectly via the activation of phospholipase D and subsequent release of phosphatidic acid (PA), a phospholipid signaling molecule. These DAG receptors act as GTPase accelerating proteins, which enhance cellular G-protein signal transduction.…”
Section: Discussionmentioning
confidence: 99%